2018
DOI: 10.2147/dmso.s184716
|View full text |Cite
|
Sign up to set email alerts
|

Diets high in vegetables, fruits, cereals, and tubers as a protective factor for metabolic syndrome in bank employees

Abstract: BackgroundThe prevalence of metabolic syndrome (MetS) is increasing, and its development may be related to westernized diets and working conditions.PurposeThe purpose of this study was to evaluate the association of dietary patterns in bank employees with the presence of MetS, considering sociodemographic and behavioral factors as well as laboratory tests.Subjects and methodsThis was a cross-sectional study of 515 bankers. Sociodemographic, occupational, behavioral, and food consumption data were collected. Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…Subsequently, 32 papers were excluded because they did not meet the inclusion criteria as follows: 9 studies considered a different dietary pattern as the comparison reference; 6 studies were carried out on adolescents; 5 studies reported the MetS risk combined with genotype; 4 studies derived the dietary patterns considering nutrients instead of food items; 3 studied reported the correlation instead of risk estimate; one study used a control group (no MetS) as reference; one study was carried out on transplant recipients; and one study was carried out on type 2 diabetes. Therefore, at the end of the selection process, 40 studies were enclosed for the identification of the different dietary patterns in the systematic review and meta-analysis [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, 32 papers were excluded because they did not meet the inclusion criteria as follows: 9 studies considered a different dietary pattern as the comparison reference; 6 studies were carried out on adolescents; 5 studies reported the MetS risk combined with genotype; 4 studies derived the dietary patterns considering nutrients instead of food items; 3 studied reported the correlation instead of risk estimate; one study used a control group (no MetS) as reference; one study was carried out on transplant recipients; and one study was carried out on type 2 diabetes. Therefore, at the end of the selection process, 40 studies were enclosed for the identification of the different dietary patterns in the systematic review and meta-analysis [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58].…”
Section: Resultsmentioning
confidence: 99%
“…These studies were published between 2007 and 2019. Eight studies were conducted in Korea [24,28,34,36,39,40,43,45], eight in Europe [20,22,31,32,41,44,52,53]; six in Iran [19,46,51,54,55,58]; four in the USA [29,37,49,50]; three in China [25,30,56]; two in Japan [33,35], Brazil [42,57], Samoan Islands [23,48] and Lebanon [21,38]; and one each in Thailand [26], Australia [27] and Mexico [47]. Four were cohort studies [36,50,53,54], one was a case-control study [25] and all others were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations